The Role of Stakeholders in The Implementation of Anemia Prevention Programs in Schools - Tursilowati, Susi; Handayani, Oktia Woro Kasmini; Yulianto, Arief; Budiono, Irwan; Pramono, Suwito Eko; Melati, Inaya (Proceedings of International Conference on Science, Education, and Technology, 2025)
The global prevalence of anemia reaches 29.9%, while in Indonesia it reaches 36.5%. Anemia in adolescent girls can lead to decreased learning ability and concentration, inhibit growth, decrease immunity, and reduce performance in physical activity. Currently, around 23% of adolescent girls in Indonesia experience anemia. As the next generation will give birth to the next generation, it is important to ensure that their nutritional, reproductive health, and hygiene needs are well met. One of the anemia control programs that can be done is through schools. The success of school-based anemia management programs is highly dependent on multisectors, including strengthening internal stakeholders and external involvement in the school environment. This study aims to find out the role of stakeholders in overcoming anemia in schools. This research method uses literature review by searching Indonesian and English articles through the Elvesier, Google Scholar and PubMed databases in the period 2015-2025. The keywords used are "anemia", "adolescents", "health programs", "schools", "stakeholders". From the results of the search and review, a number of articles were obtained used for this research. The results of the study show that stakeholders have an important role in anemia management programs in adolescent girls. Each stakeholder has their own role in supporting each other in the implementation of school-based anemia management programs in adolescents. With cooperation between stakeholders, the anemia management carried out will be more optimal.